Character Value Education through Krama Javanesse Habituation for Early Age Children - Joko Murjito (ATTARBIYAH: Journal of Islamic Culture and Education, 2018)
The habituation of speaking Krama Javanese for early age, especially in Central and East Java people is very important, because in Krama Javanese   Language contains values of character education that can shape the noble personality of children. But in reality, Krama Javanese is currently marginalized due to the wave of globalization. Krama Javanese is only used during official ceremonies (such as temanten), and in turn it will become a foreign language in his native land. This paper is the result of field research in SD Negeri 1 Demang and MI Miftahul 'Ulum Canden Sambi Boyolali. The approach used is a qualitative method. Findings; 1) Krama Javanese can form the character of students, it is better to create an environment that encourages students to behave, act politely and show respect for people who must be respected, it may also be the expectations of people who feel older or honorable for gain respect with use smooth language; 2) The use of Javanese manners in Javanese society is a means of guard toward harmonious social interaction.